Transformer Oil Dielectric Strength in the Contact Gap of the Explosive Arc-Extinguishing Device; IOP Conference Series: Materials Science and Engineering; Vol. 189 : Modern Technologies for Non-Destructive Testing - Muravlev I. O. Igor Olegovich; Surkov M. A. Michael Aleksandrovich; Tarasov E. V. Evgeny Vladimirovich; Tsoggerel Kh.; Uvarov N. F. (2017, 2017)
Title screen